Scritti a margine - Felice Ciro Papparo (Fuori Collana, 2020)
Are we made of spirit or body? Or are we a «third thing», as Nietzsche said almost 140 years ago? The question is not trivial. If, on the one hand, God's death does not allow us to trust in the immortal soul that takes away from the torments of the flesh to be destined for final judgement, on the other hand, a mechanistic scientific vision reduces everything to the body, understood as a pure piece of matter, impoverishing our vital experience. Beyond these two moments, Nietzsche intuits a space that remains to be explored, which is both physical and moral, biological and social. This book continues and deepens a research work on Nietzsche started by Papparo over 25 years ago, first with La passione senza nome (1995), then with Qualcosa del corpo (2016), taking in analysis not only the texts of the German philosopher, but his most recent interpretations. Not only Heidegger (and the French philosophy of the second half of the twentieth century: Bataille, Deleuze or Derrida), but some "friend" thinkers: Stiegler, Masullo, Giametta, Moroncini, Mazzarella, Vitiello, Giugliano... An incessant comparison that gives this book the peculiar physiognomy of a book written on the margins of the many texts examined